Sejarah Muhammadiyah di Sulawesi Selatan 1926-1942 - Darmawijaya Darmawijaya; Irwan Abbas (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
By the early 20th century, South Sulawesi is characterized by the strengthening of the Government of the Netherlands East Indies and the weakening of traditional authority. In addition, marked also by the presence of Islamic reform movement. Jamiyatul Mardiyah, Sarekat Islam, Shirathal Mustaqim and the Muhammadiyah Islamic reform organizations active in South Sulawesi, but in four of these organizations, Muhammadiyah it only works well developed. In this context, interesting articles to be presented, as it will try to answer the question, why Muhammadiyah able to thrive in the community of South Sulawesi in the period 1926-1942?Keywords: Muhammadiyah, Gerakan Modernis dan Sulawesi Selatan